A procedure of determining carbon-13 composition in soil organic carbon on an Isotope Ratio Mass-Spectrometer - Nguyen Thi, Hong Thinh; Vu, Hoai; Ha, Lan Anh; Trinh, Van Giap; Nguyen, Van Vuong (Nuclear Science and Technology, 2018)
In this study, a procedure of determining the 13C isotope composition ([13C]/[12C]) in soil organic carbon (SOC) using an isotope ratio mass spectrometer (IRMS) was developed. The procedure would be a useful approach in the studies on carbon sequestration that is of great concern among environmentalists worldwide nowadays. The procedure includes: drying, crushing, sifting and removing carbonate in soil samples before the analysis on the mass spectrometer. Results showed that the developed procedure gained a good repeatability of 0.21 ‰. The accuracy of the procedure was checked by analyzing a surrogate soil sample, a mixture of soil with known δ13CSOC and IAEA-CH-3 cellulose standard.